Rocky intertidal fish assemblage of the Watamu Marine National Park, Kenya (Western Indian Ocean) - Sindorf, Victoria; Cowburn, Benjamin; Sluka, Robert D. (Environmental biology of fishes, 2015)
The tropical rocky intertidal is a poorly studied ecosystem of great ecological and commercial importance, warranting consideration when implementing coastal management strategies. Icthyofaunal diversity was studied at low tide in intertidal pools in the Watamu Marine National Park, Kenya (Western Indian Ocean). A total of 235 individuals in 15 families (34 species) were observed in 78 sampled quadrats. Gobiidae was the most prevalent family, comprising 25.5 % of individuals (five species), followed by Blenniidae with 18.3 % of individuals (five species), Pomacentridae with 15.7 % of individuals (ten species), and Labridae with 14 % of individuals (seven species). A Chao2 asymptotic richness estimate gave an expected asymptotic richness value of 96.36 (s.d. = 6.26), but is likely an underestimate of actual species richness due to limitations of visual census techniques. Half of species observed (52.7 %) were only observed as juveniles, indicating that these habitats may function as nurseries for reef-associated and deeper water fish. Other species were resident in this zone, with ten species being found in no other habitat in the surrounding area. This study suggests that the rocky intertidal contributes greatly to adjacent subtidal reef fish populations, which may support continuing local fisheries commerce through spillover of valuable species into the fishable waters. Conservation of this habitat may be of more importance than was previously considered due to its recent discovery as a possible nursery ground for offshore coral reef fish and the presence of species not found in other habitats in the area.